Pengaruh Promosi, Citra Merek, dan Kualitas Produk Terhadap Keputusan Pembelian di Holland Bakery Unit Depok - Putri, Tyas Nova Eka (Journal of Management and Economics Innovation, 2025)
This study aims to analyze the influence of promotion, brand image, and product quality on consumer purchasing decisions at Holland Bakery Unit Depok. The research method used is a descriptive quantitative approach with data collection through questionnaires distributed to 150 respondents using accidental sampling techniques. The results of the data analysis using multiple linear regression tests indicate that the variables of promotion and product quality have a significant influence on purchasing decisions, while the brand image variable does not show a significant influence. The F-test shows that all three independent variables simultaneously influence purchasing decisions with a significance level of 0.005 (<0.05). Meanwhile, the coefficient of determination (R²) value of 12.6% indicates that promotion, brand image, and product quality together explain the purchase decision variable, while the remaining 87.4% is explained by other variables outside the research model. This study recommends the need for continuous innovation in promotions and product quality improvement to maintain consumer loyalty, as well as brand image strengthening strategies to have a more significant impact on purchasing decisions.